Supporting part-time students in doctoral programs: a technology-based situated learning model. (5th April 2021) - Zhang, Shaoan; Carroll, Mark; Li, Chengcheng; Lin, Emily
Abstract : Purpose: This paper aims to expand the theory of situated learning with the application of technology and provides a technology-based situated learning model with suggestions for doctoral program design. Design/methodology/approach: A literature review of the relevant topics was conducted. Themes emerged by the systematic review of the relevant studies and theoretical framework. Findings: Studies reveal that part-time doctoral students often feel unsupported, dissatisfied and disconnected with their program. Many of these issues may be mitigated by faculty and peer mentoring, and various forms of asynchronous communication through a situated learning framework with interactive communication technologies. Research limitations/implications: Research of doctoral education should pay more attention to part-time doctoral students and investigate the quality of their programs given their individual needs, and how their progression and completion can be achieved through the innovative approaches proposed in this study. Practical implications: Program designers may use a technology-based situated learning approach in program design to fulfill part-time doctoral students' needs toward enhancing mentorship, students' academic self-efficacy and career preparation. Further support is offered through a virtual community of practice. Social implications: This paper draws researchers' attention to program design and part-time doctoral students' retention and completion of a doctoral program. Originality/value: This study provides an innovative synergetic model that helps administrators and program designers to design doctoral programs and motivates researchers to conduct research regarding part-time doctoral students.